HEAT CONDUCTIVITY IN THERMOELECTRIC MATERIALS - I.I. Anarboyev; M.Turg‘unboyev (Лучшие интеллектуальные исследования, 2024)
Abstract: The production of thermoelectric materials and their efficiency improvement is mainly based on the thermoelectric effect. The thermoelectric effect is the direct conversion of temperature differences into electrical voltage through a thermocouple. Conversely, when a voltage is applied to it, heat flows from one side to the other, creating a temperature difference.